Letter to State Hospital Boards of Trustees; From Daniel Blain - Daniel Blain:::::: (1960)
A letter to the State Hospital Boards of Trustees from Daniel Blain (Director of Mental Hygiene) sent on September 27, 1960. This letter is to update board of trustees on scheduled meetings and other upcoming events such as discussing salary issue and public representation for California's state hospital.